Investigating L2 speech production through verbal reports : a systematic review of recent studies - Chong, Yin Sheun; Bahiyah Abdul Hamid,; Normalis Amzah,; Khazriyati Salehuddin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Introspective verbal reports have been incorporated into many studies on L2 reading and writing. In contrary, they are less utilised in studies on L2 listening and speaking. The objective of this review is to describe the use of verbal reports in recent studies on L2 speech production. The studies were identified through a comprehensive search across two (2) online databases: the Education Resources Information Center (ERIC) database and the Language and Speech (LAS) journal database. In particular, the search was restricted to studies published in the past ten (10) years (January 2012 to December 2021). A total of six (6) studies on different aspects of L2 speech production that met the predetermined selection criteria were identified and reviewed. All of the studies are set within the ESL/EFL context. The review resulted in two (2) major findings. Firstly, the verbal reports in recent studies on L2 speech production are all retrospective reports or stimulated recalls. Secondly, the verbal reports mostly played the role of triangulation to confirm and explain the data from other research instruments about the main construct being studied. Moreover, verbal reports revealed the psycholinguistic processes behind L2 learners’ speech including processes associated with bilingual speech production. Based on the review’s results, suggestions related to the use of verbal reports in future studies on L2 speech production were made.